Readiness of drivers to provide first aid depending on driving experience - V. V. Maslyakov; S. A. Sidel'nikov; A. V. Savchenko; D. A. Tyapkina; A. A. Boroday (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
Introduction. Every driver of a vehicle must be able to provide first aid (FA). Ignorance of the rules of FA can lead to untimely or poor quality of its provision and consequently to an increase in disability and mortality of people involved in a road traffic accident (RTA). Purpose: to assess the level of knowledge about the rules for providing FA, depending on the driving experience. Materials and methods. An anonymous survey was conducted among drivers of vehicles in the city of Krasnoarmeysk. The survey involved 85 respondents who were divided into three groups. Group 1 (n = 30) - drivers with less than 2 years of experience; group 2 (n = 30) - drivers with experience from 10 to 15 years; group 3 (n = 25) - drivers with more than 25 years of experience. In the course of the survey, the level of knowledge about FA was assessed, the readiness to provide it and experience in this, possible reasons for the low level of knowledge about FA and possible ways to improve it. Results. Group 1 drivers are more informed (96,7 %) regarding the designation of the place of an RTA and the rules for calling an ambulance. Respondents of the 1st group also remember best and can put into practice FA. There is a decrease in the level of theoretical and practical knowledge, depending on the increase in driving experience. Respondents of group 1 considered the lack of practice on mannequins in driving schools to be the reason for the decrease in knowledge, drivers of groups 2 and 3 - the lack of updating old knowledge about FA; also, some drivers pointed to the low level of education in driving schools. The higher the driving experience and the lower the level of knowledge about FA, the higher the desire of drivers to increase the level of knowledge and make classes or courses to improve them mandatory and regular. Conclusion. Young drivers have a fairly good level of theoretical and practical knowledge about the provision of FA, drivers with more than 10-15 years of experience have a rather low level of knowledge. Many drivers will not be able to apply this knowledge in life on their own. Therefore, in our opinion, it is necessary to introduce mandatory regular courses or classes in order to increase the level of knowledge about FA.